The Factors Influencing Mental Workload And Body Posture In Musculoskeletal Disorders: A Study On Small-Scale Tempeh Chip Industry - Malasari, Silvina Malasari; Siringoringo, Hotniar Siringoringo (JURNAL TEKNIK INDUSTRI, 2025)
Musculoskeletal disorders (MSDs) frequently occur in repetitive and static work environments, particularly within small-scale food industries. This study examines the relationship between mental workload and body posture in relation to musculoskeletal complaints. It identifies individual and psychosocial factors that influence work activities in small-scale tempeh chip production. The research was conducted on 12 active workers (5 males and seven females) at a home-based tempeh chip processing industry in Depok, West Java. Data were collected using the NASA-TLX to assess mental workload, the REBA method to evaluate body posture, and the Nordic Body Map (NBM) to measure musculoskeletal complaints. Statistical analyses included linear regression, ANOVA, and Pearson correlation to examine the relationships among variables before and after ergonomic interventions. The results revealed a significant relationship between mental workload and musculoskeletal complaints (p < 0.05). At the same time, body posture showed no statistically significant effect (p > 0.05) but demonstrated a strong interaction with mental workload (p < 0.05). Individual and psychosocial factors contributed substantially to mental workload (R² = 86.7%) and body posture (R² = 77.2%). Following ergonomic interventions—comprising a combination of sit–stand work positions, workstation adjustments, micro-breaks, and the reduction of environmental disturbances—musculoskeletal complaints decreased by approximately 60%, and mental workload was reduced to a low category. This study confirms that ergonomic interventions effectively reduce mental workload and the risk of musculoskeletal disorders. The findings provide empirical and policy contributions to the implementation of sustainable ergonomic and periodic posture training in small-scale or MSME industries to enhance worker health, safety, and productivity.